2017
DOI: 10.1002/jbm.b.34024
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole‐coated electrodes show thickness‐dependent stability in different conditions during 42‐day follow‐up in vitro

Abstract: Electroconductive polypyrrole/dodecylbenzenesulphonate (PPy/DBS) has been proposed as novel electrode coating for biomedical applications. However, as yet, little is known about its long-term stability in moist conditions. This study compares the stability of PPy/DBS-coated platinum electrodes that are either dry-stored, incubated, or both incubated and electrically stimulated. The electrical and material properties of three different coating thicknesses were monitored for 42 days. Initially, the PPy/DBS-coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The impedance of PLA‐Au‐PPy MN array with the polymerization charge of 300, 400, and 500 mC cm –2 were 956, 1108, and 3666 Ω in 1 Hz matching the frequency of the human motion, indicating the impedance of PPy film increase with the film thickness. [ 37 ] Cyclic voltammetry (CV) was applied to explore the redox behavior of PLA‐Au‐PPy MNs. As shown in Figure 3g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance of PLA‐Au‐PPy MN array with the polymerization charge of 300, 400, and 500 mC cm –2 were 956, 1108, and 3666 Ω in 1 Hz matching the frequency of the human motion, indicating the impedance of PPy film increase with the film thickness. [ 37 ] Cyclic voltammetry (CV) was applied to explore the redox behavior of PLA‐Au‐PPy MNs. As shown in Figure 3g.…”
Section: Resultsmentioning
confidence: 99%
“…[ 39 ] While under pulsed electrical stimulation, PPy film continuously transforms between oxidation and reduction states, which maintains the conductivity of PPy film and promotes the diffusion of drugs, resulting in higher drug release efficiency. [ 37 ] Further, we explored the biocompatibility of the microneedle materials and the anti‐inflammatory activity of Dex released from the MNP with RAW 267.4 cells in vitro. The results showed that the viability of the cells was above 85% (Figure S8c, Supporting Information), and the concentration of the pro‐inflammatory mediators IL‐6 and TNF‐α induced by LPS was obviously decreased after treatment with Dex from the sc‐TDDS (Figure 4h,i).…”
Section: Resultsmentioning
confidence: 99%
“…One such biocompatible material is polypyrrole (PPy), composed of heterocyclic molecules with five members, including four carbons and one nitrogen, featuring conjugated double bonds [ 5 ]. Due to their broadly tailorable properties, PPy coatings have a broad range of different biomedical application areas, such as tissue engineering scaffolds, implant coatings, drug delivery devices, and recording and stimulation applications [ 6 ]. Electrically conductive polymers, such as PPy, have undergone extensive research for their applications as active electrode materials and supporting additives across various domains, including electronics, batteries, electrodes, and biomaterials [ 7 ].…”
Section: Introductionmentioning
confidence: 99%